Cell-free fetal DNA as a non-invasive method using pyrosequencing in detecting beta-globin gene mutation: A pilot study from area with limited facilities in Indonesia - Maskoen, Ani Melani; Rahayu, Nurul Setia; Laksono, Bremmy; Fibriani, Azzania; Soewondo, Willyanti; Mose, Johanes C.; Sahiratmadja, Edhyana; Panigoro, Ramdan (Frontiers in Pediatrics, 2022)
Background: Thalassemia is a monogenic, autosomal recessive, inherited disorder of the red blood cells caused by mutations or deletions in the globin gene. Approximately 6–10% of the Indonesian population carries the β-globin gene mutation; however, premarital screening is rarely conducted and antenatal screening is optional. We explored the use of cell-free fetal DNA (cffDNA) as a potential noninvasive method of detecting the fetal β-globin gene mutation prenatally in pregnant women. Methods: Pregnant mothers (n = 10), who were known carriers of thalassemia and who had a history of having borne a baby with thalassemia major, and their carrier husbands (n = 4) were recruited after providing consent. EDTA blood was drawn, and maternal DNA, including cffDNA, and paternal DNA were isolated. Maternal contamination tests were conducted using the variable number tandem repeat test for ApoB and D1S80 loci. Allele quantification was performed by pyrosequencing. Known mutations from the bio-archived DNA of patients with thalassemia major (n = 16) were run alongside as a control. Results: In total, 7 out of 10 cffDNA successfully passed the maternal contamination test. The results of the allele quantification showed that six fetuses were carriers of IVS1nt5 and one was normal, in line with the allele quantification for the bio-archived DNA from persons with thalassemia major. Conclusion: Taking cffDNA from the mother’s blood proved useful as a noninvasive means of detecting the β-globin gene mutation using pyrosequencing allele quantification. This noninvasive method is of great interest for prenatal diagnosis in settings with limited facilities, as it minimizes the risk of abortion. Further study of other mutations of the β-globin gene is needed.